Gaya Bahasa Sindiran dalam Konten Podhub di Youtube Deddy Corbuzier - Firda Nurmaya Sinta; Encil Puspitoningrum; Andri Pitoyo (INDO PUBLISHING, 2026)
This study aims to describe sarcastic language style, meaning, and function in PODHUB content on Deddy Corbuzier’s YouTube channel. Theoretically, this research uses a descriptive approach, while methodologically it applies stylistic analysis with a qualitative design. The data source is Deddy Corbuzier’s YouTube channel, and the researcher acts as the main instrument. Data collection techniques include watching videos, identifying and documenting sarcastic expressions, transcribing spoken data into written form, classifying the data, and describing it. Data analysis is conducted descriptively, and validity is tested through peer checking. The findings show irony (6), cynicism (14), sarcasm (18), satire (6), and innuendo (1), with sarcasm as the most dominant type. The meanings of sarcasm include humorous, entertaining, and serious elements. Its functions include expressing opinions, emphasis, information, prohibition, questions, commands, and comparisons. In conclusion, various types, meanings, and functions of sarcastic language are found in the content.